2022
DOI: 10.7150/ijbs.76425
|View full text |Cite
|
Sign up to set email alerts
|

CPNE8 Promotes Gastric Cancer Metastasis by Modulating Focal Adhesion Pathway and Tumor Microenvironment

Abstract: Little is known about the oncogenic role or biological function of copine Ⅷ (CPNE8) in gastric cancer (GC). Based on TCGA database, we screened for CPNE8 and analyzed the expression of CPNE8 in GC. The correlations between CPNE8 and clinical features were analyzed using TCGA and GEO databases. The prognostic value of CPNE8 was assessed using Cox analysis and Kaplan-Meier curves. The results showed that increased express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…In breast cancer, glucose metabolism levels could be promoted by stabilizing p53-induced SERPINE1 in the miR-1185-2-3p-GOLPH3L pathway [ 42 ]. Enhanced CPNE8 expression samples was related to clinical characteristics and was predictive of unfavorable survival of patients with gastric cancer [ 43 ]. Those data supported the reliability of the current prognostic model developed using the four genes.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, glucose metabolism levels could be promoted by stabilizing p53-induced SERPINE1 in the miR-1185-2-3p-GOLPH3L pathway [ 42 ]. Enhanced CPNE8 expression samples was related to clinical characteristics and was predictive of unfavorable survival of patients with gastric cancer [ 43 ]. Those data supported the reliability of the current prognostic model developed using the four genes.…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesion is crucial in the invasiveness and metastasis of tumors. Zhang et al 19 observed the involvement of CPNE8 in regulating focal adhesion and TME to improve progression and invasiveness in gastric cancer, indicating its potential as a novel prognostic biomarker. Collagen is the principal structural protein and a vital constituent of the ECM, possessing paramount importance.…”
Section: Discussionmentioning
confidence: 99%
“…The GO enrichment analysis showed that dysregulated circRNAs significantly impact cell growth, proliferation, apoptosis, differentiation, survival, motility, and metabolism, which are crucial in the tumorigenesis and development of osteosarcoma. The results of the KEGG pathway analysis identified several important signaling pathways, including focal adhesion, which plays a critical role in cell migration, invasion, and angiogenesis during cancer progression [ 34 , 35 ]. The FoxO signaling pathway is involved in key cellular processes in cancer, such as cell differentiation, proliferation, apoptosis, DNA damage, and repair [ 36 ].…”
Section: Discussionmentioning
confidence: 99%